Peran Guru Bimbingan Konseling dalam Meningkatkan Motivasi Belajar Peserta Didik - Muzakki Anwar; Solae Mad A Lee; Hamas Nahi Munkar; Tri Kurniawan; Mujiburrohman Mujiburrohman (Indo Publishing, 2026)
This study aims to analyze the role of guidance and counseling teachers in improving students’ learning motivation. The research employed a qualitative approach using a library research method. The research data were obtained from various literature sources, such as books, scientific journals, articles, and previous studies relevant to the research topic. Data collection techniques were carried out through documentation, reading, understanding, and recording information related to the role of guidance and counseling teachers and students’ learning motivation. The data were then analyzed descriptively using content analysis techniques. The results of the study indicate that guidance and counseling teachers have an important role in helping students improve their learning motivation, overcome academic and personal problems, and develop their potential optimally. Learning motivation is an important factor that influences students’ success in the learning process. Students who have high learning motivation tend to be more active, independent, disciplined, and enthusiastic in achieving academic goals. Therefore, guidance and counseling services are highly needed in schools to support the academic, social, and personal development of students comprehensively.